2019
DOI: 10.3389/fmicb.2019.02708
|View full text |Cite
|
Sign up to set email alerts
|

Vesicles From Vibrio cholerae Contain AT-Rich DNA and Shorter mRNAs That Do Not Correlate With Their Protein Products

Abstract: Extracellular vesicles secreted by Gram-negative bacteria have proven to be important in bacterial defense, communication and host–pathogen relationships. They resemble smaller versions of the bacterial mother cell, with similar contents of proteins, LPS, DNA, and RNA. Vesicles can elicit a protective immune response in a range of hosts, and as vaccine candidates, it is of interest to properly characterize their cargo. Genetic sequencing data is already available for vesicles from several bacterial strains, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…Second, the relative abundance of several RNAs between two environmental conditions was different in the EVs and the EV-producing cells. Other studies also found that some RNA populations were enriched in EVs from Gram-negative and Gram-positive pathogenic bacteria ( Ghosal et al, 2015 ; Koeppen et al, 2016 ; Resch et al, 2016 ; Malabirade et al, 2018 ; Malge et al, 2018 ; Han et al, 2019 ; Langlete et al, 2019 ; Zhang et al, 2020 ). This notably includes sRNAs, which can play regulatory activity in the host ( Koeppen et al, 2016 ; Malabirade et al, 2018 ; Langlete et al, 2019 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Second, the relative abundance of several RNAs between two environmental conditions was different in the EVs and the EV-producing cells. Other studies also found that some RNA populations were enriched in EVs from Gram-negative and Gram-positive pathogenic bacteria ( Ghosal et al, 2015 ; Koeppen et al, 2016 ; Resch et al, 2016 ; Malabirade et al, 2018 ; Malge et al, 2018 ; Han et al, 2019 ; Langlete et al, 2019 ; Zhang et al, 2020 ). This notably includes sRNAs, which can play regulatory activity in the host ( Koeppen et al, 2016 ; Malabirade et al, 2018 ; Langlete et al, 2019 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…Other studies also found that some RNA populations were enriched in EVs from Gramnegative and Gram-positive pathogenic bacteria (Ghosal et al, 2015;Koeppen et al, 2016;Resch et al, 2016;Malabirade et al, 2018;Malge et al, 2018;Han et al, 2019;Langlete et al, 2019;Zhang et al, 2020). This notably includes sRNAs, which can play regulatory activity in the host (Koeppen et al, 2016;Malabirade et al, 2018;Langlete et al, 2019;Zhang et al, 2020). The enrichment of RNAs associated with bacterial diseases in EVs derived from many pathogenic bacteria reinforces the physiopathological role of these structures in host-pathogen interaction and host cell invasion, which could be borne by their RNA cargo as well as by their protein cargo.…”
Section: Discussionmentioning
confidence: 94%
“…Sometimes fusion of vesicles have resulted in formation of filamentous structures, also known as nanopods or nanotubes (Dongre et al, 2011 ; Dubey and Ben-Yehuda, 2011 ; Gill et al, 2018 ). EVs may contain virulence factors (Devos et al, 2015 ; Askarian et al, 2018 ; Wagner et al, 2018 ; Nadeem et al, 2020 ), such as toxins (Rivera et al, 2010 ; Coelho et al, 2019 ) as well as other enzymes (Smalley and Birss, 1987 ; Elhenawy et al, 2014 ), quorum sensing molecules (Mashburn and Whiteley, 2005 ; Brameyer et al, 2018 ; Morinaga et al, 2018 ) and nucleic acids such as DNA (Hagemann et al, 2014 ; Bitto et al, 2017 ; Langlete et al, 2019 ) and RNA (Sjöström et al, 2015 ; Koeppen et al, 2016 ; Choi J.-W. et al, 2017 ). Their content may vary depending on species and growth conditions (Bager et al, 2013 ; Ghosal et al, 2015 ; Koeppen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The surface of these vesicles is composed of lipopolysaccharide (LPS), phospholipids and outer membrane proteins [ 19 , 20 ]. The vesicular lumen, however, contains periplasmic and cytoplasmic components, including genetic material and virulence factors, such as invasion associated factors, toxins, and immune response modulators [ 21 , 22 , 23 ]. Thermolabile toxins and cytolysin have been identified in OMVs produced by Escherichia coli [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%